Evolution shapes and conserves genomic signatures in viruses - Holmudden, Martin; Gustafsson, Joel; Bertrand, Yann J K; Schliep, Alexander; Norberg, Peter (Communications biology, 2024)
The genomic signature of an organism captures the characteristics of repeated oligonucleotide patterns in its genome 1, such as oligomer frequencies, GC content, and differences in codon usage. Viruses, however, are obligate intracellular parasites that are dependent on their host cells for replication, and information about genomic signatures in viruses has hitherto been sparse.Here, we investigate the presence and specificity of genomic signatures in 2,768 eukaryotic viral species from 105 viral families, aiming to illuminate dependencies and selective pressures in viral genome evolution. We demonstrate that most viruses have highly specific genomic signatures that often also differ significantly between species within the same family. The species-specificity is most prominent among dsDNA viruses and viruses with large genomes. We also reveal consistent dissimilarities between viral genomic signatures and those of their host cells, although some viruses present slight similarities, which may be explained by genetic adaptation to their native hosts. Our results suggest that significant evolutionary selection pressures act upon viral genomes to shape and preserve their genomic signatures, which may have implications for the field of synthetic biology in the construction of live attenuated vaccines and viral vectors.
Keywords: molekulární evoluce; viry; selekce (genetika); druhová specificita; Genomics; Codon Usage; genom virový; Selection, Genetic; využití kodonu; genomika; fylogeneze; Viruses; Phylogeny; Genome, Viral; Species Specificity; Evolution, Molecular